P481 Profile of elderly patients in which biological drugs are used for the treatment of inflammatory bowel disease. (21st January 2022) - Suarez Ferrer, C J; Mesonero, F; Caballol, B; Ballester, M P; Baston Rey, I; Castaño Garcia, A; Miranda Bautista, J; Saiz Chumillas, R; Benitez, J M; Sanchez Delgado, L; Lopez-Garcia, A; Rubin de Celio, C; et al.
Abstract: Background: The use of biological drugs for the treatment of IBD in elderly patients is becoming more frequent in our environment. However, given the greater risk of these patients to develop related adverse effects, the profile of the patients in whom it is applied and the type of drug to choose, has not been established. Methods: Patients have been retrospectively included with established diagnosis of IBD UC, CD or indeterminate colitis (IC) by usual criteria (clinical, laboratory, endoscopic, radiological and / or histological) 65 years at the time of initiating biological treatment (Infliximab, Adalimumab, Golimumab, Ustekinumab or Vedolizumab) and that they have received at least the induction doses. Variables corresponding to the baseline characteristics of the patients have been collected, as well as data referring to the characteristics of IBD that have been considered relevant for the study. We calculated the comorbidity of the patients using the Charlston index The statistical analysis was completed using Stata 15.0. For continuous variables, after checking the normality of the distribution, were compared using t Student and categorical variables chi2 test for proportions Results: 1090 biological treatments started in patients aged 65 years or older have been retrospectively included. The baseline characteristics are summarized in TABLE 1 and those related to his IBD in TABLE 2.most used treatments in order of frequency were: Infliximab (377, 34.8%), Adalimumab(311, 28.7%), Golimumab (28, 2.6%), Ustekinumab (157, 14.5%) and Vedolizumab (209, 19.3%). It should be noted that most of the patients had monotherapy treatment, finding only 27.7% (299 patients) combined with immunosuppressants (IMS) (thiopurines in 72.9% of cases). Identify 705 patients (64.8%) had a Charlston score = <1 (absence of comorbidity), 219 patients (20.13%) 2 points (low comorbidity) and 164 (15.07%) score => 3 points (high comorbidity). It was objective that the choice of the type of biological could be conditioned by the presence of comorbidity, presenting 22% of the patients (66 cases) who opted for Ustekinumab / vedolizumab high comorbidity versus 15% of patients with antiTNF (98 cases) with high comorbidity. (p = 0.012). It was investigated whether the antecedent of neoplasia influenced the choice of biological treatment, finding that 47% of the cases (72 patients) opted for antiTNF and in 53% (80 patients) by ustekinumab / vedolizumab, these differences being statistically significant(p <0.0001) Conclusion: In our experience, biological drugs with different therapeutic targets are used in elderly patients, generally in non-frail patients.The use of more specific treatments(ustekinumab, vedolizumab)is preferred in those with greater associated comorbidity